The Effect Of Career Perception, Economic Motivation, Taxation Knowledge, And Labor Market Consideration On Career Interest In Taxation - Wijaya, Rahayu; Rusaktiva Rustam, Akie (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The large contribution of taxes to a country creates extensive career opportunities in taxation sector. However, the small number of tax officers and tax consultants in Indonesia requires efforts to stimulate student career interest in taxation. This study, as such, aims to examine the effect of career perceptions, economic motivation, taxation knowledge, and labor market considerations on student career interest in taxation both partially and simultaneously. The population of this study include undergraduate accounting students of Universitas Brawijaya, from which 118 samples are selected through purposive sampling. This study used a quantitative method to analyze the data. The data collected through questionnaires are analyzed by multiple linear regression models processed by SPSS 30. The results of this study exhibit that partially economic motivation and labor market considerations have a significant effect on student career interest in taxation while career perceptions and taxation knowledge have no effect on student career interest in taxation.